Lizards and tortoises show evidence of low inhibitory control - Maria Santacà; Anna Wilkinson; Gionata Stancher; Valeria Anna Sovrano; Angelo Bisazza (Scientific Reports)
Abstract Inhibitory control, the ability to suppress an automatic response in favour of a contextually appropriate alternative, is crucial for adaptive behaviour across animal species. While extensively studied in mammals and birds, research on reptiles remains limited, with comparisons hindered by methodological inconsistencies. Here, we assessed inhibitory control in two reptile species, Hermann’s tortoise (Testudo hermanni) and the bearded dragon (Pogona vitticeps), using the transparent cylinder test—a method widely employed with mammals, birds, and fish. This test evaluates the ability to inhibit reaching directly for visible food through a transparent barrier. Both species exhibited lower inhibitory control than most amniotes, supporting the prevalent hypothesis linking inhibitory capacity to brain size. However, exceptions observed in various species suggest ecological and non-cognitive factors also shape these abilities. Notably, bearded dragons outperformed tortoises, despite their smaller size. In tortoises, females surpassed males, highlighting sex-based inhibitory differences in non-avian reptiles. Additionally, a positive correlation between lateralization and inhibitory control was observed in both species, providing the first evidence of such a link in reptiles. These findings emphasize the role of lateralization in reptilian cognition and suggest that inhibitory control across vertebrates is influenced by diverse factors, including brain size, ecology, and sex.